2009
DOI: 10.1017/s0033291709990729
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in cannabis use: a systematic review of the literature

Abstract: Background. We conducted a systematic review to assess the evidence for specific effects of cannabis on brain structure and function. The review focuses on the cognitive changes associated with acute and chronic use of the drug.Method. We reviewed literature reporting neuroimaging studies of chronic or acute cannabis use published up until January 2009. The search was conducted using Medline, EMBASE, LILACS and PsycLIT indexing services using the following key words : cannabis, marijuana, delta-9-tetrahydrocan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
153
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 93 publications
10
153
2
2
Order By: Relevance
“…Impaired cognition in chronic cannabis users is thought to be underpinned at least in part, by alterations to the regulatory role of the endocannabinoid system on synaptic plasticity following prolonged and regular exposure to exogenous cannabinoids such as THC (Hampson et al, 2011;Heifets and Castillo, 2009;Hoffman et al, 2007;Puighermanal et al, 2012). In light of deficits in cognition (e.g., selective attention, verbal learning and inhibition, Solowij and Michie, 2007), and alterations in brain function (e.g., prefrontal cortical, cingular, hippocampal and cerebellar activation in imaging studies, Solowij and Michie, 2007;Martin-Santos et al, 2010) and structure (e.g., reduced hippocampal volume, Yücel et al, 2008b) in long-term cannabis users being similar to those observed in patients with schizophrenia, further investigation of neurobiological markers of pre-attentive processes may inform mechanisms by which cannabis might result in schizophrenia-like conditions in the brain and induce psychosis in vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired cognition in chronic cannabis users is thought to be underpinned at least in part, by alterations to the regulatory role of the endocannabinoid system on synaptic plasticity following prolonged and regular exposure to exogenous cannabinoids such as THC (Hampson et al, 2011;Heifets and Castillo, 2009;Hoffman et al, 2007;Puighermanal et al, 2012). In light of deficits in cognition (e.g., selective attention, verbal learning and inhibition, Solowij and Michie, 2007), and alterations in brain function (e.g., prefrontal cortical, cingular, hippocampal and cerebellar activation in imaging studies, Solowij and Michie, 2007;Martin-Santos et al, 2010) and structure (e.g., reduced hippocampal volume, Yücel et al, 2008b) in long-term cannabis users being similar to those observed in patients with schizophrenia, further investigation of neurobiological markers of pre-attentive processes may inform mechanisms by which cannabis might result in schizophrenia-like conditions in the brain and induce psychosis in vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to animal literature, results from human studies investigating chronic cannabis users are often inconsistent. These discrepancies may be due to heterogeneity in socio-demographic characteristics of the population studied, imaging techniques employed, as well as differences in drug usage patterns and psychiatric comorbidities that may not always be apparent or result in contact with mental health services and hence may not be appropriately controlled for in studies where participants are screened for presence of co-morbid psychiatric disorder merely by enquiring about previous contact with mental health services [28][29][30]. However, overall the results suggest that long-term cannabis use may result in persistent alterations in brain function and morphology that would extend beyond the period of intoxication [28,31], and that earlier onset of use may be associated with greater detrimental effects [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The growing concern about cannabis use has led to a significant increase in the number of human studies using neuroimaging techniques to determine the effect of the substance on brain structure and function, as well as to several recent reviews examining this topic [28,29,34,[41][42][43][44][45][46]. However, some authors have only reviewed studies investigating the acute effects of cannabis [45,46] or those published over the last decade [41,44], while others did not adequately specify criteria for selecting studies [41,43] or included those studies that investigated only adult population [29,42].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations